Effect of rear impact on the instrumented cervical spine: a finite element study - Harinathan, Balaji; Jebaseelan, Davidson; Yoganandan, Narayan (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionDegenerative cervical myelopathy (DCM) is a leading cause of spinal cord dysfunction and often requires surgical decompression and instrumentation. Anterior cervical discectomy and fusion (ACDF) is the most commonly performed procedure, but the biomechanical response of instrumented cervical spines under rear-impact loading remains unclear.MethodsA validated finite element model of the head–neck complex with active musculature, spinal cord, and three instrumented constructs was used to simulate a low-speed rear impact corresponding to a 2.6 m/s change in velocity. The following surgical conditions were modeled at C4–C7: ACDF, posterior cervical laminectomy and fusion (PCLF), and laminoplasty (LP). Spinal cord stress and strain, ligament strain (including anterior longitudinal and capsular ligaments), and implant stress were evaluated at the index, superior, and inferior segments.ResultsCompared to ACDF, both PCLF and LP reduced spinal cord stress and strain at the index level, with PCLF showing the greatest reduction. LP preserved motion but increased facet capsular ligament strain at the index and adjacent levels. Anterior longitudinal ligament strains remained below 36%, within the reported 40–45% failure range, while PCLF screws exceeded the 900 MPa yield strength of Ti–6Al–4V at all levels except C4, indicating a reduced hardware safety margin. ACDF and LP implants remained within safe stress limits.ConclusionUnder rear-impact loading, PCLF reduced spinal cord stress and strain relative to ACDF but increased hardware stresses, whereas LP preserved motion at the cost of higher facet capsular ligament strain. These findings suggest that PCLF may be preferred when minimizing spinal cord loading is a priority, while LP may be selected when motion preservation is critical, with awareness of construct-specific trade-offs in ligament and implant loading.